NATURAL PARASITIZATION ON LEAFMINER, CHROMATOMYIA HORTICOLA (GOUREAU) (DIPTERA: AGROMYZIDAE) IN FIELD PEA - SUNIL KUMAR YADAV; SHWETA PATEL (The Bioscan, 2015)
The present paper reports the occurrence of two hymenopteran parasitoids of Agromyzid leaf miner, Chromatomyia horticola (Goureau) (Diptera: Agromyzidae) from Pantnagar (India). The parasitoids recorded were Diglyphus sp. (Eulophidae: Hymenoptera) and Opius sp. (Braconidae: Hymenoptera). The activity of C. horticola commenced during 52th standard week (Dec. 23 to Dec. 29) and it attained peak during the 7th standard week (Fab. 12 to Fab. 18). The per cent parasitization during course of investigation ranged from 5.26 to 58.13% (mean=27.21±15.92). The peak period of parasitization was observed during 11th standard week (Mar. 12 to Mar. 18) at 58.13 per cent of parasitization. The variations of temperature, relative humidity and rainfall caused approximately 64, 42 and 20 per cent of the variation in the per cent parasitization, respectively. The number and diversity of parasitoid species at Pantnagar has the potential to effectively control Chromatomyia horticola.